2022
DOI: 10.1080/23808985.2022.2069046
|View full text |Cite
|
Sign up to set email alerts
|

Dating apps: a literature review

Abstract: Dating apps have become one of the most prominent and contentious topics in the realm of intimacy among the wider public and academia. Media and communication researchers have examined their uptake across cultural contexts, seeking to address the dynamics between dating apps and social processes. With the knowledge accumulated in this research field, we assemble a comprehensive account of interactions through dating apps. We categorize existing findings about dating apps into three sections: dating apps and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 97 publications
2
6
0
Order By: Relevance
“…The data show that Grindr is used for diverse reasons in the tourism context that extend beyond arranging casual sexual encounters, even in the case of tourists visiting for a short term. This supports the findings in the literature on Grindr (Corriero & Tong, 2016;Shield, 2017;Wu & Trottier, 2022) about its multiple uses. Furthermore, this research indicates that Grindr tourism in fact entails a bundle of practices which will be expanded upon below, which can range from an interaction on Grindr as small as getting a restaurant recommendation from a local without ever meeting in person, or an in-person date that constitutes of a guided tour of the city.…”
Section: Findings and Discussion: Practices Of Grindr Tourismsupporting
confidence: 91%
See 1 more Smart Citation
“…The data show that Grindr is used for diverse reasons in the tourism context that extend beyond arranging casual sexual encounters, even in the case of tourists visiting for a short term. This supports the findings in the literature on Grindr (Corriero & Tong, 2016;Shield, 2017;Wu & Trottier, 2022) about its multiple uses. Furthermore, this research indicates that Grindr tourism in fact entails a bundle of practices which will be expanded upon below, which can range from an interaction on Grindr as small as getting a restaurant recommendation from a local without ever meeting in person, or an in-person date that constitutes of a guided tour of the city.…”
Section: Findings and Discussion: Practices Of Grindr Tourismsupporting
confidence: 91%
“…A common cultural assumption is that Grindr is used solely to arrange casual sex. Yet studies have found that people use Grindr for multiple social reasons (Brubaker et al, 2014; Shield, 2017; Wu & Trottier, 2022), many of which are evident in the “looking for” drop-down menu options on Grindr profiles whereby users can state their intentions as “chat, dates, friends, networking, relationship, and right now” (a euphemism for casual sex). Interactions on Grindr may be situated within contexts of sex and relationships, but my intention in this article is to highlight other interactions that diverge from the “label” of casual sex often associated with Grindr (although these interactions may occur within relations that are sometimes sexual, and in such instances in the data, this will be discussed).…”
Section: Situating Grindr Tourism In the Literaturementioning
confidence: 99%
“…According to our survey, the number of “stranger” social app users in China is still rising. Dating apps have become a prominent and contentious topic in discussions over intimacy among the wider public and in academia (Wu and Trottier, 2022 ). Chan ( 2020 ) conducted a detailed empirical study of the multiple uses of Momo, a popular Chinese dating app.…”
Section: Introductionmentioning
confidence: 99%
“…Online dating has received considerable attention in the past decades from various academic disciplines (see Wu and Trottier (2022) and Degim et al (2015) for comprehensive literature overviews). Yet, it is not our aim to provide a literature review of this body of research because we are not directing our lens to different aspects concerning how people use or perceive dating sites per se.…”
Section: Algorithms and Recommendation Systemsmentioning
confidence: 99%